EXAMINING THE RELATIONSHIP BETWEEN COMPETENCY, MOTIVATION, WORKABILITY, AND PERFORMANCE IN THE INDONESIAN NAVY: A STRUCTURAL EQUATION MODELING APPROACH - Arianto Wibowo (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2023)
The success of an organization is intricately linked to the caliber of its human resources. The performance of personnel serves as a fundamental gauge of their quality. Consequently, in order to fulfill the vision of the Indonesian Navy, enhancing the quality of its human resources takes precedence. The program implemented to bolster soldier performance involves equipping them with competence through comprehensive education, training, and personnel development initiatives. Motivation plays a pivotal role in this process, and several measures are taken to foster it. These measures include augmenting welfare benefits, providing career coaching, and bestowing rewards upon exceptional personnel. By synergizing the Competency Variables (X1) and Motivation (X2), the aim is to enhance Work Ability (Z), ultimately leading to elevated Performance (Y) levels and attaining optimal outcomes. The present research employs structural equation modeling to examine the influence of these variables, thereby generating valuable insights into which factors exert the greatest impact on soldier performance. By conducting this study, the intent is to offer precise data pertaining to the variables that wield the most influence over soldier performance. Consequently, the findings will enable the provision of more accurate suggestions and recommendations. Armed with this knowledge, the Indonesian Navy can refine its strategies for enhancing human resource quality, thus fostering an environment conducive to superior performance. Moreover, the research outcomes will contribute to the broader understanding of factors that contribute to organizational success, serving as a guide for other institutions seeking to optimize their workforce performance. Keywords: Structure Equation Modeling (SEM), Influence Test, Soldier Performance, Motivation, Second Fleet Command